WELFARE STATE: LUMPUH SEKALIGUS MELUMPUHKAN - Qusthan Abqary H. F. (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
Welfare state on traditional or modern form still remain some weakness. On traditional form, welfare state’s emerge high burden on state budget. On the other hand, modern form of this idea was failure to finishing some classic problem— unemployment and poverty as such. This paper explores some critiques to welfare state ideas. And the most important thing is, welfare state paralysing individual’s autonomy for the sake of a reason which embodied as so called commodity: welfare.